Pengaruh konsenterasi dan ukuran bank serta inflasi terhadap stabilitas bank pembangunan daerah - Yudaruddin, Rizky (INOVASI, 2017)
The research aims to study the impact of the country's economic conditions and interest rates rill home country and the host country of the loan especially in foreign bank in Indonesia. The data used are secondary data in the form of financial statements of foreign banks starting in 2003 - 2013. The analytical tool used in this research is panel data regression. The study found a relationship between economic conditions home country of the foreign bank lending in the host country and a significant negative. For the host country economic conditions, showed positive and significant relationship towards lending in the host country. As for the variable interest rate home country has a positive and significant relationship with a foreign bank lending in the host country. While the variable interest rate host country has a significant positive relationship and not with foreign bank lending in the host country